2022
DOI: 10.1039/d2cp02030k
|View full text |Cite
|
Sign up to set email alerts
|

Mode selective chemistry for the dissociation of methane on efficient Ni/Pt-bimetallic alloy catalysts

Abstract: The mode selectivity of methane dissociation is studied on three different Ni/Pt-bimetallic alloy surfaces using a fully quantum approach based on reaction path Hamiltonian. Dissociative sticking probability depends on the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 114 publications
(273 reference statements)
0
2
0
Order By: Relevance
“…18 The findings of a more recent study, which were reported by Akça, showed that CH 4 dissociation on the bimetallic Pd/Cu(111) surface was more favorable than that on the monometallic Cu(111) surface. 19 Roy and his colleagues concluded in a recent study that surface modification with Pt/Ni(111) 20 and Ni/Pt(111) 20,21 alloys resulted in enhanced and efficient catalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…18 The findings of a more recent study, which were reported by Akça, showed that CH 4 dissociation on the bimetallic Pd/Cu(111) surface was more favorable than that on the monometallic Cu(111) surface. 19 Roy and his colleagues concluded in a recent study that surface modification with Pt/Ni(111) 20 and Ni/Pt(111) 20,21 alloys resulted in enhanced and efficient catalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Under normal conditions, both surface strain and ligand effects simultaneously modify the electronic structure and chemical properties of bimetallic surfaces. Consequently, extensive experimental and theoretical investigations have been conducted to examine their influence on reactivity. …”
mentioning
confidence: 99%